Potensi Pengolahan Salami (Sosis Fermentasi) Daging Kambing - Hakim, Arief Rahman; Haris, Helmi; Akil, Syahrir (Jurnal Ilmiah Pangan Halal, 2023)
Goats are ruminants that can take advantage of low-quality forage for basic needs and production. Goat can be used as an alternative to consuming processed beef products. One of the processed beef products is salami. Salami is one of the processed meats made from a mixture of meat and fat that is made through a fermentation process. The process of processing salami involves fermentation. This fermentation uses a starter made from lactic acid bacteria. The bacteria usually used in making salami are lactic acid bacteria, namely Lactobacillus bulgaricus, Streptococcus thermophilus, and Lactobacillus acidophilus. Salami usually uses a mixture of pork and beef as a base, but it is possible to make it from other livestock meat, for example, Goats. Salami from pork is not allowed for Islamic consumers because it is forbidden according to Islamic religion, while salami from beef has a costly price compared to the price of goat meat.